Investigating how researcher-defined buffers and self-drawn neighbourhoods capture adolescent availability to physical activity facilities and greenspaces: An exploratory study. (November 2022) - Christensen, A.; Radley, D.; Hobbs, M.; Gorse, C.; Griffiths, C.
Highlights: This study compares 30 different definitions of researcher-defined neighbourhoods and self-drawn neighbourhoods to objectively measured availability. Findings show low agreement for all researcher-defined buffers and self-drawn neighbourhoods in measuring the availability of PA facilities (low PPV values, low sensitivity values, or both). Results were less clear for greenspace with a 400 metre network line ellipse reporting high agreement (PPV and sensitivity >50%). This study highlights the inadequacy of researcher-defined buffer to capture adolescent availability to environmental features. Abstract: Background: Modifying the environment is considered an effective population-level approach for increasing healthy behaviours, but associations remain ambiguous. This exploratory study aims to compare researcher-defined buffers and self-drawn neighbourhoods (SDN) to objectively measured availability of physical activity (PA) facilities and greenspaces in adolescents. Methods: Seven consecutive days of GPS data were collected in an adolescent sample of 14–18 year olds ( n = 69). Using Points of Interest and greenspace data, availability of PA opportunities within activity spaces were determined. We compared 30 different definitions of researcher-defined neighbourhoods and SDNs to objectively measured availability. Results: :Findings showed low agreement for all researcher-defined buffers in measuring the availability of PA facilities in activity spaces. However, results were less clear for greenspace. SDNs also demonstrate low agreement for capturing availability to the PA environment. Conclusion: This exploratory study highlights the inadequacy of researcher-defined buffers and SDNs to define availability to environmental features.